Reflecting on my reflexivity within a constructivist grounded theory study on team coaching: A short report - Fox, Sebastian (European Journal for Qualitative Research in Psychotherapy, 2023)
This short report shares my experiences as a doctoral student when engaging reflexivity in my research and, in particular, when grappling with constructivist grounded theory methodology and carrying out data generation.  It sets out my philosophical paradigm, the context for the research, my understanding of the term “reflexivity” and the different lenses through which I am being reflexive in my thesis.